Report on AIDS in the United Kingdom and recommendations for Malaysia - Ismail , Rokiah ([not specified], 1990)
I was given the opportunity to study the AIDS situation in the United Kingdom. This was possible with the grant provided by the Association of Commonwealth Universities through their Commonwealth Senior Medical Fellowship programme.